Hazard Identification, Risk Assessment and Determining Control (HIRADC) in Mining Operations at PT Semen Padang - Fadhilah Fadhilah; Elita Amrina; Risma Erwi Gusvita (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
The mining industry has potential and hazard factors with high risks and are prone to accidents. Based on the records of work accidents that occurred at PT Semen Padang in 2022, 67% often occur in the mining operation unit. This study aims to identify hazard risks, analyze the severity of each risk and its risk category as well as risk control in the mining operational area of PT Semen Padang. This research is a qualitative research with a descriptive approach using risk analysis in the form of likelihood and consequences as well as risk matrix analysis. This method is a form of risk management process as an effort to prevent work accidents. Based on the research results, there are 30 types of hazard risks found in the mining operational area with a percentage of risk level, namely 67% low risk level, 27% medium risk level, and 6% high risk level. Industri pertambangan memiliki potensi dan faktor bahaya dengan risiko yang tinggi dan rentan terhadap kecelakaan. Berdasarkan rekaman kecelakaan kerja yang terjadi di PT Semen Padang pada tahun 2022, sebesar 67% sering terjadi di unit operasi tambang. Penelitian ini bertujuan untuk mengidentifikasi risiko bahaya, menganalisis tingkat keparahan setiap risiko dan kategori risikonya serta pengendalian risiko yang terdapat di area operasional tambang PT Semen Padang. Penelitian ini merupakan penelitian kualitatif pendekatan deskriptif menggunakan analisis risiko dalam bentuk kemungkinan dan konsekuensi serta analisis matriks risiko. Metode ini merupakan bentuk proses manajemen risiko sebagai upaya pencegahan kecelakaan kerja. Berdasarkan hasil penelitian terdapat 30 jenis risiko bahaya yang ditemukan di area operasional penambangan dengan persentase tingkat risiko yaitu 67% tingkat risiko rendah, 27% tingkat risiko sedang, dan 6% tingkat risiko tinggi.